English Undergraduate Students and Their Metacognitive Awareness Level: Evidence from One English Education Program - Bunga Ayu Wulandari; Ahmad Ridha; Fortunasari Fortunasari (Indonesian Research Journal in Education |IRJE|, 2022)
This research investigated students’ level of metacognitive awareness and its correlation with their grade point average (GPA). The data derived from 166 English department students at an Indonesian teacher training faculty who responded to the Metacognitive Awareness Inventory (MAI) instrument developed by Schraw and Dennison (1994). The statistical analysis of the data collected showed the mean MAI score for the 166 participants in this study was 41.54. It also showed metacognitive regulation has a higher mean score (28.45) than metacognitive knowledge (13.09). Pearson correlation analysis indicated that there is no significant correlation between students’ metacognitive awareness and their GPA (sig. 0,46 > 0,05). It means that students with high metacognitive awareness levels can have lower GPAs, whereas those with low levels of metacognitive awareness can have higher GPAs.